Studien zu queeren Lesarten der Hebräischen Bibel - Hügel, Karin (Biblical interpretation series, 2026)
"Studien zu queeren Lesarten der Hebräischen Bibel (Studies on Queer Readings of the Hebrew Bible) deals with non-normative sexualities in the Hebrew Bible and related Jewish and Christian exegetical writings. The book presents queer readings of these sources which are developed within the framework of intertextuality. Apart from Hebrew Bible passages and rabbinic sayings that build upon them, European works of art from the Renaissance, the Baroque, and the 19th century addressing pederasty, effeminate men or sexually ambivalent figures are discussed. These works confirm that quasi-queer interpretations were already extant prior to contemporary scholarly biblical interpretations. Studien zu queeren Lesarten der Hebräischen Bibel befasst sich mit nicht normativen Sexualitäten in der Hebräischen Bibel und damit verbundenen jüdischen und christlichen exegetischen Schriften. Das Buch präsentiert queere Lesarten dieser Quellen, welche im Rahmen von Intertextualität entwickelt werden. Neben Textpassagen der Hebräischen Bibel und rabbinischen Aussagen im Anschluss an sie werden europäische Kunstwerke der Renaissance, des Barocks und des 19. Jahrhunderts besprochen, welche Knabenliebe, effeminierte Männer oder sexuell ambivalente Figuren thematisieren. Diese Werke bestätigen, dass es quasi queere Interpretationen bereits vor den heutigen wissenschaftlichen Bibelauslegungen gab"-- Provided by publisher